Peer evaluation and co-evaluation applied to professionalizing degrees: Application in the building engineering degree - Saéz-Pérez, Mª Paz; Robles Sánchez, Susana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The acquisition of the competences of a subject established in the study plan encourages the search for new methods that improve the teaching-learning process, especially in the qualifications that enable the exercise of a profession with legal attributions. Through this text, the results of the application of the peer evaluation system and the co-evaluation of the subject Valuations of Real Estate and Expert reports of the Degree in Building Engineering are explained throughout 5 academic years, allowing to conclude the benefits on the acquisition of skills and improvement of success rates, as well as the implementation of professional powers.